Technological change and human resource development practices in Asia: a study of Singapore-based companies - Osman-Gani, Aahad M.; Jacobs, Ronald L. (Blackwell Publishing Ltd., 2005)
Technological change is a constant phenomenon in contemporary organizations. How to prepare employees for technological change has increasingly become an issue for human resource development theory and practice. This study investigated the human resource development practices of organizations in Singapore, where companies are continuously responding to rapid technological changes in order to remain competitive. The results show similar patterns of responses across business sectors; however, some differences were found in the transport and communications sectors. On-the-job training was reported as the most frequently used training method to address organizational change needs. The discussion and recommendations focus on the need for improved change management approaches.